Ink resistant to multiple times of stacked coating and preparation method thereof

Through the composite and nanofiller design of epoxy acrylate and polyurethane prepolymer, the problems of gloss attenuation, insufficient adhesion and poor weather resistance after multiple stacking of traditional inks are solved, and high gloss and strong adhesion inks are achieved, which are suitable for high-end digital printing and functional coating fields.

CN120349678APending Publication Date: 2025-07-22SUZHOU XIONGYING INK NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510656807.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-21
Publication Date
2025-07-22

AI Technical Summary

Technical Problem

Traditional inks are prone to problems such as gloss attenuation, insufficient adhesion and poor weather resistance after multiple coatings.

Method used

The combination of epoxy acrylate and polyurethane prepolymer is used to regulate cross-linking density and flexibility, combined with the mechanical support of the nanofiller and the synergistic effect of the sustained release agent, the nano-encapsulated hindered amine light stabilizer and UV absorber extend the UV aging time, and the appropriate mixed solvents and surfactants are combined to improve gloss and adhesion.

Benefits of technology

Maintain excellent gloss and adhesion after multiple stacking, extending weather resistance, suitable for a variety of substrates, suitable for high-end digital printing and functional coating fields.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an ink resistant to multiple stacked coating and a preparation method thereof, the ink comprises the following raw materials by mass: 43-47% of a resin matrix, 8-12% of a nano filler, 4-6% of a slow release agent, 3-5% of a photoinitiator, 32-38% of a composite solvent and 1-3% of an adhesion leveling additive, and the invention relates to the technical field of writing and drawing material inks. According to the ink resistant to multiple times of stacked coating and the preparation method thereof, through combination of high crosslinking density of epoxy acrylate and flexibility of polyurethane and mechanical support of stacked core-shell nanofiller, the ink is still free of a cracking or stripping phenomenon after multiple times of stacked coating, and due to the synergistic effect of the nano-coated hindered amine light stabilizer and the UV absorbent, the ink has a good anti-cracking effect. The ultraviolet aging resistance time of the ink is effectively prolonged, the volatilization rate of a mixed solvent is adapted in cooperation with the wide absorption spectrum of 2, 4, 6-trimethylbenzoyl-diphenyl phosphine oxide, it is ensured that a thick ink coating is evenly cured, the color stability is improved, the surface glossiness is improved in cooperation with a fluorocarbon surfactant, and meanwhile the ink has good base material adaptability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of inks, and specifically to an ink with resistance to multiple overcoats and a preparation method thereof. Background Art

[0002] The performance of ink resistance to multiple overcoats is a key technical bottleneck restricting the quality and application scope of its application products. Traditional inks are prone to the following defects after multiple overcoats: Gloss attenuation: After multiple coatings, the surface roughness of the coating increases and light scattering enhances, resulting in a significant decrease in gloss; Insufficient adhesion: The interfacial bonding force between coatings is weak, prone to cracking and peeling; Poor weather resistance: Under the action of ultraviolet rays and humidity, pigments and resins are prone to decomposition, resulting in fading and powdering.

[0003] Although existing water-based ink absorption coatings have excellent ink absorption performance, their gloss and adhesion decrease significantly after multiple overcoats; while watercolor inks improve the color overlapping effect by coating dyes with water-soluble resins, but they have poor weather resistance and are prone to fading.

[0004] Based on the retrieval of the above-mentioned information, a kind of ink with resistance to multiple overcoats and a preparation method thereof are specifically proposed, providing an ink with resistance to multiple overcoats that combines excellent weather resistance, high gloss retention rate and strong adhesion. Summary of the Invention

[0005] Aiming at the deficiencies of the prior art, the present invention provides an ink with resistance to multiple overcoats and a preparation method thereof, solving the problems that traditional inks are prone to gloss attenuation, insufficient adhesion and poor weather resistance after multiple overcoats.

[0006] To achieve the above object, the present invention is realized through the following technical solutions: An ink with resistance to multiple overcoats, the raw materials of which include, by mass percentage: 43-47% of resin matrix, 8-12% of nano filler, 4-6% of slow-release agent, 3-5% of photoinitiator, 32-38% of composite solvent and 1-3% of adhesion and leveling additive.

[0007] The present invention is further set as: The resin matrix includes epoxy acrylate and polyurethane prepolymer, and the epoxy acrylate and polyurethane prepolymer include, by mass ratio: 9-11:1-3, wherein the DA bond density of epoxy acrylate is 3.2-3.5 mmol / g.

[0008] The present invention is further set as: The nano filler is a microcapsule core-shell particle with silica as the core and titanium dioxide and polydopamine as the core-shell, and the mass ratio of silica, titanium dioxide and polydopamine is: 12-14:3-6:1-3; The particle size of the microcapsule core-shell particle is 75-80 nm, and the specific surface area is 550-650 m2 / g.

[0009] The present invention is further configured such that: the slow-release agent includes a hindered amine light stabilizer and a UV absorber encapsulated by polyurethane, the hindered amine light stabilizer is UV-123, the UV absorber is 2-hydroxy-4-n-octyloxybenzophenone, wherein the mass ratio of the hindered amine light stabilizer to the UV absorber is 2-4:1-3, and the particle size D50 of the slow-release agent is 25-28 nm.

[0010] The present invention is further configured such that: the photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and the 2,4,6-trimethylbenzoyl-diphenylphosphine oxide uses toluene as a solvent with a concentration of 5-6 wt%.

[0011] The present invention is further configured such that: the composite solvent includes ethyl acetate and isopropanol, and the mass ratio of ethyl acetate to isopropanol is: 3-4:1-2.

[0012] The present invention is further configured such that: the adhesion and leveling additive includes a silane coupling agent and a fluorocarbon surfactant, the silane coupling agent is KH560 silane coupling agent, the fluorocarbon surfactant is a polyoxyethylene ether-based fluorocarbon surfactant, and the weight ratio of the silane coupling agent to the fluorocarbon surfactant is 4-6:1-2.

[0013] The present invention provides an ink resistant to multiple overcoats and a preparation method thereof. It has the following beneficial effects: (1) By combining the high crosslinking density of epoxy acrylate with the flexibility of polyurethane and superimposing the mechanical support of the core-shell nano-fillers, the ink shows no cracking or peeling after multiple overcoats. The synergistic effect of the nano-encapsulated hindered amine light stabilizer and the UV absorber effectively extends the UV aging time of the ink. Cooperating with the broad absorption spectrum of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide to adapt to the evaporation rate of the mixed solvent ensures uniform curing of the thick ink coating, improves color stability, and cooperates with the fluorocarbon surfactant to enhance the surface gloss, while having good substrate adaptability.

[0014] (2) By compounding epoxy acrylate and polyurethane prepolymer to regulate the balance of crosslinking density and flexibility, it not only ensures the hardness and scratch resistance of the cured ink but also avoids cracking caused by the accumulation of internal stress after multiple overcoats. The slow release of the stabilizer is achieved through nano-level encapsulation, extending the weather resistance of the coating.

[0015] (3) By enhancing the interfacial bonding force between the filler and the resin through the polydopamine shell layer, titanium dioxide provides UV shielding and hiding power, and the silica core enhances the mechanical strength. Detailed implementation mode

[0016] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Apparently, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.

[0017] The embodiments of the present invention provide the following technical solutions: Embodiment 1. An ink resistant to multiple overcoats, the raw materials of which include, by mass percentage: Resin matrix 44%, the resin matrix includes epoxy acrylate and polyurethane prepolymer, and the polyurethane prepolymer is the product of model L200 provided by Covestro. The epoxy acrylate and the polyurethane prepolymer include, by mass ratio: 9:1, wherein the DA bond density of the epoxy acrylate is 3.2 mmol / g. The DA bond is a covalent bond formed through the Diels-Alder reaction. The Diels-Alder reaction is a [4+2] cycloaddition reaction, in which a conjugated diene (Diels olefin) reacts with a dienophile (Alder reagent) to form a six-membered ring compound, that is, a cyclohexene derivative. In this process, two new carbon-carbon σ bonds will be formed, and these two bonds are the DA bonds; Nanofiller 10%, the nanofiller is a microcapsule core-shell particle with silica as the core and titanium dioxide and polydopamine as the core shell. The silica, titanium dioxide and polydopamine include, by mass ratio: 13:5:2; The particle size of the microcapsule core-shell particle is 80 nm, and the specific surface area is 650 m 2 / g; Release agent 5%, the release agent includes a hindered amine light stabilizer and a UV absorber encapsulated by polyurethane. The hindered amine light stabilizer is selected as UV-123, and the UV absorber is selected as 2-hydroxy-4-n-octyloxybenzophenone. The hindered amine light stabilizer and the UV absorber include, by mass ratio: 3:2, and the particle size D50 of the release agent is 28 nm; Photoinitiator 4%, the photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, that is, TPO-L. Using toluene as the solvent, the concentration of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide is 6 wt%; Composite solvent 35%, the composite solvent includes ethyl acetate and isopropyl alcohol. The ethyl acetate and the isopropyl alcohol include, by mass ratio: 3:1; Adhesion and leveling additive 2%, the adhesion and leveling additive includes a silane coupling agent and a fluorocarbon surfactant. The weight ratio of the silane coupling agent to the fluorocarbon surfactant is 4:1. The silane coupling agent is KH560 silane coupling agent, and the fluorocarbon surfactant is selected as a polyoxyethylene ether-based fluorocarbon surfactant, and its structural formula is: CF3(CF2)7O(CH2CH2O) 10 H.

[0018] Further description: The preparation method of the nano filler includes: A1. Weigh tetraethyl orthosilicate, absolute ethanol and deionized water according to the molar ratio of 1:4:12. After mixing, add 28wt% ammonia water to adjust the pH to 9.5, and stir at a constant temperature of 40°C for 24h. Tetraethyl orthosilicate hydrolyzes under alkaline conditions to form silica sol. After sealing and standing for 72h, centrifuge at 12000rpm for 15min, and wash three times with ethanol solvent to obtain nano-silica. Among them, by adjusting the concentration of tetraethyl orthosilicate and the addition amount of ammonia water, the particle size is accurately controlled to be 80nm; A2. Disperse the nano-silica in deionized water to obtain a dispersion solution. The dispersion ratio is: nano-silica: deionized water = 1g: 50mL. Add a 2wt% mixture to the dispersion solution. The mixture is concentrated sulfuric acid and 30% hydrogen peroxide with a volume ratio of 3:1. The addition ratio of the mixture to nano-silica is: 35mL: 1g. Reflux at 80°C for 12h to complete the surface hydroxylation modification of nano-silica; A3. Disperse the nano-silica in isopropanol, ultrasonically treat it at a power of 300W for 30min, add tetrabutyl titanate and urea. Among them, the mass ratio of tetrabutyl titanate to nano-silica is 1:3, and the addition amount of urea is 10% of the total system. Stir magnetically at 800rpm for 15min to obtain a precursor solution, transfer it to a high-pressure reaction kettle, and react at 180°C for 24h. Grow anatase-type titanium dioxide shell layer with a thickness of 10nm on the surface of nano-silica by solvothermal method, then carry out centrifugal washing, and calcine at 450°C for 2h to obtain semi-finished product particles; A4. Disperse the semi-finished product particles in Tris-HCl buffer solution with pH = 8.5, ultrasonically treat until evenly dispersed, add 2mg / mL dopamine hydrochloride, stir magnetically at 200rpm for 6h, self-polymerize to form a polydopamine layer with a thickness of 5±1nm, centrifuge and wash at 10000rpm for 10min, and vacuum dry at 40°C for 12h to obtain the nano filler.

[0019] Further description: The preparation method of the slow-release agent includes: B1. Mix the hindered amine light stabilizer and the UV absorber according to the mass ratio of 3:2, dissolve them in 35wt% ethyl acetate, ultrasonically disperse at 40kHz for 30min until D90<50nm, add 0.5wt% ammonium polyacrylate dispersant, HLB = 12.5, to prevent nano-particle aggregation. In a supercritical CO2 environment of 30MPa / 50°C, use a high-pressure microfluidic homogenizer to process at a pressure of 250MPa to obtain a monodisperse core liquid, PDI<0.1; B2. Mix the monodisperse core liquid and isophorone diisocyanate in a molar ratio of 1:1.2, add 0.1 wt% dibutyltin dilaurate catalyst to obtain the oil phase. After mixing 3 wt% polyvinyl alcohol and 0.5 wt% sodium dodecyl sulfate, add NaOH solution to adjust the pH to 8.5 to obtain the aqueous phase. Drop the oil phase into the aqueous phase, with the mass ratio of the oil phase to the aqueous phase being 1:4, and perform high-speed shear emulsification at 12000 rpm for 10 min to form an emulsion. Heat up to 60 °C and react for 6 h to form a polyurethane shell layer through the cross-linking of —NCO and —OH groups; B3. Centrifuge the reaction solution (8000 g, 15 min) to remove the uncoated particles, then wash it 3 times with a methanol aqueous solution with a mass ratio of 30%. Perform dynamic focusing using a microfluidic chip with a channel width of 50 μm, and adjust the flow rate ratio: the washed reaction solution: methanol aqueous solution = 1:10 to make D50 stable at 28 nm. Perform spray drying at an inlet temperature of 120 °C and an outlet temperature of 60 °C to obtain a free-flowing powder with a moisture content <0.5%, which is the sustained-release agent.

[0020] The preparation method of the ink resistant to multiple overcoating specifically includes the following steps: S1. Mix the resin matrix, nano-fillers, and sustained-release agent, and stir at 1000 rpm for 30 min at a constant temperature of 25 °C. Add a photoinitiator and a composite solvent, stir at 1000 rpm for 1 h, add an adhesion and leveling additive, and stir at 1000 rpm for 15 min to obtain a premixed solution; S2. Grind the premixed solution using a three-roll mill with a roll speed difference ratio of 2:1, grind 3 times, filter it with a 0.45 μm polytetrafluoroethylene filter membrane, and then perform degassing for 30 min at a vacuum degree of -0.09 MPa and an environment temperature of 25 °C to obtain the finished ink.

[0021] Example 2. The difference between this example and Example 1 is: An ink resistant to multiple overcoating, the raw materials of which include, by mass percentage: 45% resin matrix, 12% nano-fillers, 6% sustained-release agent, 4% photoinitiator, 32% composite solvent, and 1% adhesion and leveling additive; The mass ratio of epoxy acrylate and polyurethane prepolymer is: 5:1, and the DA bond density of epoxy acrylate is 3.5 mmol / g; The mass ratio of silica, titanium dioxide, and polydopamine is: 14:3:3; The particle size of the microcapsule core-shell particles is 78 nm, and the specific surface area is 620 m 2 / g; The mass ratio of the hindered amine light stabilizer and the UV absorber is 4:1, and the particle size D50 of the sustained-release agent is 27 nm; 2,4,6-Trimethylbenzoyl-diphenylphosphine oxide uses toluene as a solvent and the concentration is 5 wt%; Ethyl acetate and isopropanol are in a mass ratio of 4:1; The weight ratio of the silane coupling agent to the fluorocarbon surfactant is 3:1.

[0022] Example 3. The difference between this example and Example 1 is as follows: A multi - layer coating - resistant ink, whose raw materials by mass percentage include: resin matrix 43%, nano - filler 8%, slow - release agent 4%, photo - initiator 5%, composite solvent 38%, and adhesion and leveling additive 2%; The mass ratio of epoxy acrylate to polyurethane prepolymer is 11:3, and the DA bond density of epoxy acrylate is 3.3 mmol / g; The mass ratio of silicon dioxide, titanium dioxide, and polydopamine is 12:6:1; The particle size of the micro - capsule core - shell particles is 75 nm, and the specific surface area is 550 m 2 / g; The mass ratio of the hindered amine light stabilizer to the UV absorber is 2:3, and the particle size D50 of the slow - release agent is 25 nm; 2,4,6 - Trimethylbenzoyl - diphenylphosphine oxide uses toluene as a solvent, and the concentration is 5 wt%; Ethyl acetate and isopropanol are in a mass ratio of 3:2; The weight ratio of the silane coupling agent to the fluorocarbon surfactant is 5:1.

[0023] Example 4. The difference between this example and Example 1 is as follows: A multi - layer coating - resistant ink, whose raw materials by mass percentage include: resin matrix 47%, nano - filler 10%, slow - release agent 5%, photo - initiator 3%, composite solvent 32%, and adhesion and leveling additive 3%.

[0024] Example 5. The difference between this example and Example 1 is as follows: A multi - layer coating - resistant ink, whose raw materials by mass percentage include: resin matrix 45%, nano - filler 11%, slow - release agent 5%, photo - initiator 4%, composite solvent 33%, and adhesion and leveling additive 2%.

[0025] Example 6. The difference between this example and Example 1 is as follows: A multi - layer coating - resistant ink, whose raw materials by mass percentage include: resin matrix 44%, nano - filler 9%, slow - release agent 4%, photo - initiator 3%, composite solvent 37%, and adhesion and leveling additive 3%.

[0026] In summary, it can be seen that the component differences between Examples 1 to 6 are shown in Table 1: Table 1 Resin matrix / % Nanofiller / % Sustained-release agent / % Photoinitiator / % Composite solvent / % Adhesion and leveling additive / % Example 1 44 10 5 4 35 2 Example 2 45 12 6 4 32 1 Example 3 43 8 4 5 38 2 Example 4 47 10 5 3 32 3 Example 5 45 11 5 4 33 2 Example 6 44 9 4 3 37 3 Ink was prepared according to the components provided in Embodiment 1 to Embodiment 6, and the performance of the prepared ink was tested. Weather resistance was tested using an ultraviolet aging chamber, curing speed was tested using a pendulum hardness tester, adhesion was tested using the cross-cut method, hiding power was tested using a black and white checkerboard, and leveling property was tested using an orange peel gauge. After testing, it was found that the ink prepared according to the components provided in Embodiment 2 had the best weather resistance, the ink prepared according to the components provided in Embodiment 3 had the best curing speed, the ink prepared according to the components provided in Embodiment 4 had the best adhesion and was suitable for substrates with large differences in expansion coefficients, the ink prepared according to the components provided in Embodiment 5 had the best hiding power and was suitable for dark or transparent substrates, and the ink prepared according to the components provided in Embodiment 6 had the best leveling property. Simulation Experiment 1: To verify the performance of the ink prepared from the components provided in Embodiment 1 of the present invention for multiple overcoating, a traditional UV ink was used as a control group, and a comparative test was carried out under the test conditions of curing energy = 800 mJ / cm², substrate = PC plastic, temperature 25°C / humidity 50%RH. Among them, adhesion was tested by the cross-cut method with a coated tape, and hardness was tested by the pencil hardness test method. The test results are shown in Table 2: Table 2 Coating times The present invention Control group 1 time Adhesion = Grade 1, hardness = 2H, no cracks Adhesion = Grade 1, hardness = HB, no cracks 3 times Adhesion = Grade 0, hardness = 3H, no cracks Adhesion = Grade 2, hardness = H, slight cracks at the edge 5 times Adhesion = Grade 0, hardness = 4H, no cracks Adhesion = Grade 3, hardness = B, obvious cracking As can be seen from Table 2, through the synergistic effect of resin compounding and core-shell fillers, excellent adhesion and anti-cracking performance were still maintained after 5 overcoatings. Among them, the adhesion grade refers to the grade specified in the ASTM D3359 standard.

[0027] Simulation Experiment 2: To verify the yellowing, gloss retention rate, and mechanical property attenuation of the ink coating under ultraviolet radiation, taking the ink prepared from the components provided in Embodiment 1 of the present invention as an example, and the ink prepared by removing the slow-release agent from the components provided in Embodiment 1 of the present invention as a control group, a comparative test was carried out under the test conditions of a UV-A lamp tube, radiation intensity = 0.8 W / m 2 , and cyclic temperature and humidity (60°C / 90%RH). Through color measurement, a color difference meter or spectrometer was used to measure the color change of the ink before and after the test, and the yellowing index was calculated. Through the photoelectric glossiness meter method, a photoelectric detector was used to measure the intensity of the reflected light on the ink surface, and the glossiness value was obtained by comparing with a standard reflector. Adhesion was tested by the cross-cut method with a coated tape. The test results are shown in Table 3: Table 3 Radiation time / h Yellowing index / Δb* Gloss retention rate / % Cross-cut adhesion / grade 0 0.0 100 0 250 1.2 85 0 500 2.1 70 1 Control group Δb* = 4.5 at 500 h 45% at 500 h Grade 3 at 500 h As can be seen from Table 3, the nano-encapsulated slow-release agent significantly improved the weather resistance. After 500 h of aging, the yellowing was only 46% of that of the control group, and the gloss retention rate was 40% higher.

[0028] Simulation Experiment 3: To verify the effects of different photoinitiators and composite solvent combinations on curing depth, hardness, and leveling property, I-184 photoinitiator was introduced and compounded with ethyl acetate and isopropyl alcohol at mass ratios of 3:1 and 4:1 respectively. Taking the ink prepared from the components provided in Example 1 of the present invention as an example, comparative tests were carried out under the test conditions of a 395 nm LED light source, curing time = 10 s / 30 s, and film thickness = 50 μm. The curing depth was evaluated by observing the appearance change of the ink layer after ultraviolet light irradiation, the hardness was tested by pencil hardness test, and the leveling property was tested by an orange peel gauge. The test results are shown in Table 4: Table 4 Formulation combination Curing depth at 10 s / μm Hardness at 30 s / H Leveling property (orange peel grade) TPO-L + 3:1 solvent 32 3 0 (smooth) I-184 + 3:1 solvent 18 2 1 (slight orange peel) TPO-L + 4:1 solvent 25 2 0 (smooth) As can be seen from Table 4, the combination of TPO-L and the 3:1 solvent reaches a 3H hardness within 30 s, the curing depth is 78% higher than that of I-184, and the surface leveling property is better.

[0029] In summary, through the design of nano-fillers and sustained-release agents and combined with an optimized preparation process, the present invention solves the deficiency of traditional inks in the performance of resisting multiple overcoats, provides a core material solution for the fields of high-end digital printing and functional coatings. The multi-component collaborative design, nano-material functionalization, and fine parameter control form innovations in the performance of resisting multiple overcoats, weather resistance, and construction performance, and are applicable to scenarios with strict requirements for coating performance in fields such as 3C electronics and automotive painting, having the technical value of replacing traditional UV inks.

[0030] It should be noted that in this article, relational terms such as first and second are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the term "comprising", "including" or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device comprising a series of elements not only includes those elements, but also includes other elements not expressly listed, or further includes elements inherent to such process, method, article or device. Although the embodiments of the present invention have been shown and described, those of ordinary skill in the art can understand that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principle and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An ink resistant to multiple overcoats, characterized in that: Its raw materials by mass percentage include: resin matrix 43-47%, nano filler 8-12%, slow release agent 4-6%, photoinitiator 3-5%, composite solvent 32-38% and adhesion and leveling additive 1-3%; The resin matrix includes epoxy acrylate and polyurethane prepolymer; The nano filler is a microcapsule core-shell particle with silica as the core and titanium dioxide and polydopamine as the core-shell; The slow release agent includes hindered amine light stabilizer and UV absorber encapsulated by polyurethane; The photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide; The composite solvent includes ethyl acetate and isopropanol.

2. The ink resistant to multiple overcoats according to claim 1, wherein: The mass ratio of the epoxy acrylate to the polyurethane prepolymer is: 9-11:1-3, and the DA bond density of the epoxy acrylate is 3.2-3.5 mmol / g.

3. The ink resistant to multiple overcoats according to claim 1, wherein: The mass ratio of the silica, titanium dioxide and polydopamine is: 12-14:3-6:1-3; The particle size of the microcapsule core-shell particles is 75 - 80 nm, and the specific surface area is 550 - 650 m 2 / g.

4. The ink resistant to multiple overcoats according to claim 1, wherein: The hindered amine light stabilizer is UV-123, the UV absorber is 2-hydroxy-4-n-octyloxybenzophenone, the mass ratio of the hindered amine light stabilizer to the UV absorber is 2-4:1-3, and the particle size D50 of the slow release agent is 25-28 nm.

5. The ink resistant to multiple overcoats according to claim 1, characterized in that: The 2,4,6-trimethylbenzoyl-diphenylphosphine oxide uses toluene as the solvent and the concentration is 5-6 wt%.

6. The ink resistant to multiple overcoats according to claim 1, wherein: The mass ratio of the ethyl acetate to the isopropanol is: 3-4:1-2.

7. An ink resistant to multiple overcoats according to claim 1, characterized in that: The adhesion and leveling additive includes silane coupling agent and fluorocarbon surfactant. The silane coupling agent is KH560 silane coupling agent, the fluorocarbon surfactant is polyoxyethylene ether fluorocarbon surfactant, and the weight ratio of the silane coupling agent to the fluorocarbon surfactant is 4-6:1-2.

8. A method for preparing an ink resistant to multiple overcoating as described in any one of claims 1-7, characterized in that: Specifically, it includes the following steps: S1. After mixing the resin matrix, nano filler and slow release agent, at a constant temperature of 25°C, stir at 1000 rpm for 30 min, add the photoinitiator and composite solvent, stir at 1000 rpm for 1 h, add the adhesion and leveling additive, and stir at 1000 rpm for 15 min to obtain a premixed liquid; S2. Grind the premixed liquid with a three-roll mill, the roll speed difference ratio is 2:1, grind 3 times, filter with a 0.45 μm polytetrafluoroethylene filter membrane, and then defoam for 30 min under a vacuum of -0.09 MPa and at an environment temperature of 25°C to obtain the finished ink.